Sudden Death Following Selective Neuronal Lesions in the Rat Nucleus Tractus Solitarii - Talman, William T. (Auton Neurosci, 2012)
In efforts to assess baroreflex and cardiovascular responses in rats in which substance P (SP) or catecholamine transmission had been eliminated we studied animals after bilateral injections into the nucleus tractus solitarii (NTS) of SP or stabilized SP (SSP) conjugated to saporin (SP-SAP or SSP-SAP respectively) or SAP conjugated to an antibody to dopamine-β-hydroxylase (anti-DBH-SAP). We found that SP- and SSP-SAP eliminated NTS neurons that expressed the SP neurokinin-1 receptor (NK1R) while anti-DBH-SAP eliminated NTS neurons expressing tyrosine hydroxylase (TH) and DBH. The toxins were selective. Thus SP-or SSP-SAP did not eliminate TH/DBH neurons and anti-DBH-SAP did not eliminate NK1R neurons in the NTS. Each toxin, however, led to chronic lability of arterial blood pressure, diminished baroreflex function, cardiac ventricular irritability, coagulation necrosis of cardiac myocytes and, in some animals, sudden death associated with asystole. However, when TH/DBH neurons were targeted and eliminated by injection of 6-hydroxydopamine (6-OHDA), none of the cardiovascular or cardiac changes occurred. The studies reviewed here reveal that selective lesions of the NTS lead to altered baroreflex control and to cardiac changes that may lead to sudden death. Though the findings could support a role for SP or catecholamines in baroreflex transmission neither is proven in that NK1R colocalizes with glutamate receptors. Thus neurons with both are lost when treated with SP- or SSP-SAP. In addition, loss of catecholamine neurons after treatment with 6-OHDA does not affect cardiovascular control. Thus, the effect of the toxins may depend on an action of SAP independent of the effects of the SAP conjugates on targeted neuronal types.